Efflorescent Sulphates with M+ and M2+ Cations from Fumarole and Active Geothermal Fields of Mutnovsky Volcano (Kamchatka, Russia) - Elena S. Zhitova; Dmitry A. Khanin; Anton A. Nuzhdaev; Maria A. Nazarova; Rezeda M. Ismagilova; Vladimir V. Shilovskikh; Anastasia N. Kupchinenko; Ruslan A. Kuznetsov; Pavel S. Zhegunov (Minerals, 2022)
In this study, sulphate efflorescent minerals covering the surface of the Donnoe and Dachnoe fields of the Mutnovsky volcano are described. The minerals were precipitated on the argillic facies as the result of water–rock interaction and fumarole emission. A chemical composition of Ca, Ba, (NH4)+, Na-Fe3+, (NH4)+-Al, (NH4)+-Fe3+, Na-Al, K-Al, and K-Fe3+ sulphates was reported. Elements such as Sr, Mg, Co, Ni, Ti and P were found as isomorphic impurities. Ammonia species were concentrated around fumaroles. The mineral assemblage described herein is unique in relation to other geological settings and reflects the process of low-temperature mineral formation associated with volcanism. The thermal water contains cations such as H, Na, K, NH4, Ca, Mg, Fe2+, Fe3+, and Al in different proportions with pH ranging from 2.4 to 6.5 and the dominance of acidic waters. The gas condensate bears such cations as (NH4)+, Ca, and Mg and has a pH of ~5. Thus, the rest of the main cations are derived from the leaching of the host rocks. Among the identified phases, the alunite-supergroup minerals are more prone to isomorphism. The Ti, Co, and Ni impurities mark the unique geochemistry of thermal water at the Mutnovsky volcano. We postulate that the chemical composition of alunite-supergroup minerals reflects the types of hydrothermal occurrences and contains important information on the geochemistry of the hydrothermal process.